2017
DOI: 10.1634/theoncologist.2016-0260
|View full text |Cite
|
Sign up to set email alerts
|

A Host-Dependent Prognostic Model for Elderly Patients with Diffuse Large B-Cell Lymphoma

Abstract: The ACA index has the ability to stratify the prognosis, tolerability to cytotoxic drugs, and adherence to treatment of elderly patients with DLBCL treated with R-CHOP. 2017;22:554-560 IMPLICATIONS FOR PRACTICE: Currently, little is known regarding how to identify elderly patients with diffuse large B-cell lymphoma who may tolerate a full dose of chemotherapy or to what extent cytotoxic drugs should be reduced in some specific conditions. The Society of Lymphoma Treatment in Japan developed a host-dependent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 22 publications
5
35
1
Order By: Relevance
“… did not find evidence for an association between CCI and choice of chemotherapy regimen or completion of treatment in their review. However, they confirm findings from several prior studies, restricted to patients who have received treatment, that CCI is associated with a higher frequency of grade III/IV toxicities, dose reductions and in the majority of studies, with inferior OS []. In line with this, the increased risk of other‐cause death associated with comorbidity amongst patients treated with curative intent in our study may be due to aggravation of prior conditions by toxic treatment regimens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… did not find evidence for an association between CCI and choice of chemotherapy regimen or completion of treatment in their review. However, they confirm findings from several prior studies, restricted to patients who have received treatment, that CCI is associated with a higher frequency of grade III/IV toxicities, dose reductions and in the majority of studies, with inferior OS []. In line with this, the increased risk of other‐cause death associated with comorbidity amongst patients treated with curative intent in our study may be due to aggravation of prior conditions by toxic treatment regimens.…”
Section: Discussionsupporting
confidence: 92%
“…The inferior overall survival amongst comorbid patients in this large cohort is in line with several prior studies []. Few prior studies have however assessed the influence of comorbidity on choice of treatment with palliative or curative intent as the majority of prior studies on comorbidity in DLBCL have been restricted to patients who have received chemotherapy . In our study, the inferior outcome was mainly due to increased other‐cause mortality amongst curatively treated comorbid patients, and by an increase in both lymphoma‐specific and other‐cause death amongst all comorbid patients, largely explained by the lower relative probability of receiving treatment with curative intent amongst patients with CCI ≥ 1.…”
Section: Discussionsupporting
confidence: 87%
“…Patients with comorbidities are more prone to treatment‐related toxicity and experience dose reductions, which might contribute to the lower rates of complete remission in elderly patients . A limited number of small studies have shown the association between comorbidities, as assessed by Charlson Comorbidity Index (CCI), and adverse outcome in DLBCL patients . This includes a recent analysis of 836 elderly (≥65 years) Japanese patients, in which a scoring system consisting of age, low serum albumin and CCI of ≥3 was able risk stratify patients for survival and treatment outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Given the retrospective design of our study, there were some missing data that could potentially affect distribution and outcome of the study. Due to limited data access, we were not able to explore significance of some other factors such as hypoalbuminemia or creatinine which were reported to have prognostic significance in older lymphoma patients [23]. However, these laboratory features could be indirectly implied by illnesses composing in CCI.…”
Section: Discussionmentioning
confidence: 95%